Pengaruh Berbagai Media Tumbuh dan Lama Pencahayaan Lampu terhadap Pertumbuhan Bibit Talipuk (Nymphaea pubescens Willd.) - Norhalidah Norhalidah; Bambang Joko Priatmadi; Yudhi Ahmad Nazari (Agroekotek View, 2019)
The purpose of this research is to know the influence of various growing media and the old lighting of lamp to growth of seedling of talipuk and also to know growing media and long best lighting lamp for growth of talipuk seedlings. This research method used Split Plot Design 2 factors with 9 treatments 3 replicates and 27 experimental units with main plot of long lighting while multiplication of growth media that was carried out in Biology Laboratory Faculty of Agriculture Universitas Lambung Mangkurat Banjarbaru South Kalimantan in July until August 2017. The results showed that the interaction between the length of lighting and the type of growth media did not significantly affect all observed variables observed. Prolonged exposure of 18-hour lamps had significant effect on leaf length and treatment of various types of growth medium significantly influenced leaf length, leaf width, and length of stalk and significantly affected leaf number, wet weight of plant and dry weight of plant, wet root weight and dry weight of the roots.